Pelaksanaan Pembelajaran Rekorder Menggunakan Aplikasi Whatsapp Di Kelas Vii.5 SMPN 2 Pariaman - Silvy Avelia Wardin; Irdhan Epria Darma Putra (FBS Universitas Negeri Padang, 2020)
This study aims to describe the implementation of recorder learning using WhatsApp application in class VII.5 at SMPN 2 Pariaman. This is a qualitative research using descriptive method. The main instrument in this study was the researcher itself and was assisted by supporting instruments such as writing instruments and cameras. The data were collected through literature study, interview, observation, and documentation. The steps for analyzing data are collecting the data, describing the data, and making conclusions. The results show that the implementation of learning using WhatsApp application at SMP Negeri 2 Pariaman, especially in class VII.5, has not been carried out well because not all students participate in the process of online learning. There are obstacles in the implementation of online learning such as internet connection, internet loads. In addition, there are still some students who do not have cellphones. As a result, there are many students who do not participate in the learning process using WhatsApp application. At the presentation and delivery stage, the teacher only gives assignments to students through group chat or voice messages on WhatsApp groups that have been made specifically for learning Cultural and Arts. The training and practice stages are not optimal because the activities cannot be directly controlled by the teacher.